Design and in vitro release study of siRNA loaded Layer by Layer nanoparticles with sustained gene silencing effect. (3rd October 2018) - Tan, Yang Fei; Lee, Ying Shi; Seet, Li-Fong; Ng, Kee Woei; Wong, Tina T.; Venkatraman, Subbu
ABSTRACT: Objectives : Clinical translation of siRNA therapeutics has been severely limited due to the lack of stable and sustained siRNA delivery systems. Furthermore, when nanocarrier systems with siRNA are administered systemically to treat diseases, insufficient doses reach the target tissue. Here we report the successful development of a new nanocarrier system for the management of fibrosis. Methods : The new carrier has a hydroxyapatite core, with alternating layers of siRNA and a cationic peptide. The siRNA used here targets secreted protein acidic and rich in cysteine (SPARC), a key matricellular protein involved in the regulation of collagen fibrillogenesis and assembly. We have also used FRET studies to elucidate the fate of the particles inside cells, including the mechanistic details of layer-by-layer detachment. Results : In vitro studies using murine conjunctiva fibroblasts show sustained release over 2 weeks, and that such released siRNA sustained SPARC knockdown without affecting cell growth, and maintained siRNA presence in the cells for at least two weeks with a single-dose treatment. Release studies of siRNA from particles in vitro gave insight on how the particles delivered prolonged gene-silencing effects. Conclusion : A single treatment of the layer-by-layer nanoparticle designed can achieve sustained gene silencing over 2 weeks. Localized delivery of stabilized siRNA with sustained-release capabilities opens the door for many other applications of siRNA-based gene regulation.